RELATIVE ATTACK ANGLE OF FIN AFFECTS THE CONVECTIVE HEAT TRANSFER - Razalee, Muhammad Reezwan Shah (IRC, 2020)
Analytical investigation is made for three-dimensional fluid flow and convective heat transfer for designed fin. This project aims to achieve the highest rate of convective heat transfer by changing the relative attack angle of fin. For analytical investigation, simulation software was used to save time and cost of the project by running multiple simulations on different attack angle of the fin. The results are compared with other simulation running with different velocity magnitude. The designed fin with perfect relative attack angle can be used in future industry that needs heat transfer application as it is more reliable and cost economical.